Energy-Momentum Distribution for Magnetically Charged Black Hole Metric - Farasat Shamir; Rida Ejaz; Mushtaq Ahmad (Journal of Mathematical Sciences and Modelling, 2020)
This work investigates the well known localization problem of energy and momentum. The purpose of this paper is two fold. First, we compute Einstein, Landau-Lifshitz and Bergmann's energy-momentum complexes for static spherically symmetric magnetically charged regular black hole spacetime in general relativity. We observe strong coincidences among the results obtained form the three descriptions. These resembling results from different energy-momentum prescriptions may offer some basis to explain a exclusive quantity which supports Virabhadra's viewpoint. Secondly, the problem is discussed in modified gravity. In particular, we use generalized Landau-Lifshitz prescription for the determination of energy-momentum with reference to $f(R)$ theory of gravity. We explicitly compute the energy-momentum complex for the static spherically symmetric magnetically consistent regular black hole metric for a well-known choice of the $f(R)$ gravity models.